Perancangan Sistem Pengiriman Logistik Pada Perusahaan Manufaktur - Purwandari, Nuraini (Sekolah Tinggi Ilmu Manajemen dan Ilmu Komputer ESQ (STIMIK ESQ), 2016)
XYZ company is a manufacturing company which engages in the field of computer peripheral. Information system in this company are not yet integrated with each other which is computerized. ERP (Enterprise Resource Planning) is a system that is built to unite all departments and functions that exist in a company into an integrated system. In the ERP contained a particular module which regulate and control the flow of goods, energy, information and other resources such as products, services, and people from the source of production to the market namely the logistics. The logistics also includes the integration of information, transportation, inventory, and warehousing. The purpose of this research is to produce a prototype design of the logistics delivery system implementation in manufacturing companies using Netbeans 8.0 software with the Java programming language and MySQL database. The method used is a model rapid prototyping is the development model by testing against aÂ working model of an application through the interaction process to meet the needs of users. The results from this research is a prototype design of the logistics delivery system in order to allow a user to see the flow of freight.